Curvature-Induced Magnetization of Altermagnetic Films - Yershov, Kostiantyn; Gomonay, Olena; Sinova, Jairo; van den Brink, Jeroen; Kravchuk, Volodymyr (Physical Review Letters, 2025)
The altermagnetic nature of a large class of magnetically ordered materials is the source of a wide range of new effects. Here, we show that the merging of two areas, namely the altermagnetism and the physics of curvilinear low-dimensional magnets gives rise to a distinct novel physical effect: a curvature-induced magnetization in bend altermagnetic films. This effect opens a promising possibility for imaging of the domain structure in the magnetically compensated structures. We consider a thin film of a 𝑑-wave altermagnet bent in a stretching-free manner and demonstrate that gradients of the film curvature induce a local magnetization that is approximately tangential to the film. The magnetization amplitude directly reflects the altermagnetic symmetry and depends on the direction of bending. It is maximal for the bending along directions of the maximal altermagnetic splitting of the magnon bands. A periodically bent film of sinusoidal shape possesses a total magnetic moment per period ∝𝒜2⁢𝑞4, where 𝒜 and 𝑞 are the bending amplitude and wave vector, respectively. The total magnetic moment is perpendicular to the plane of the unbent film and its direction (up or down) is determined by the bending direction. A film roll-up to a nanotube possesses a toroidal moment directed along the tube ∝𝛿𝑟/𝑟2 per one coil, where 𝑟 and 𝛿𝑟 are the coil radius and the pitch between coils. All these analytical predictions agree with numerical spin-lattice simulations.